Determinantes de la calidad del gobierno corporativo de los bancos hondure\~nos; Determinants of corporate governance quality of Honduran banks - Sorto Murillo; Telma Osiris (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The purpose of this study is to determine a system of indicators to assess the quality of corporate governance of Honduran banks. To achieve it, the importance attributed by bank supervisors and supervised bankers to the dimensions and indicators of Corporate Governance (CG) was deepened. Therefore, the differences between both groups were identified to create a CG quality index with indicators that exceed a global mean greater than 3.5 on the Likert scale of 1-5 and the relative weight of dimensions. The focus of this research is quantitative, with a correlational scope and a nonexperimental, cross-sectional design. A survey was applied to officials of the banking system and bank supervisors, whose scale has reliability with a Cronbach's Alpha, 0.961 and the normality tests reflect acceptable scores (using the two-step model). The results indicate that the most important dimension is "relations with shareholders" with a relative weight of 20.73%, "effectiveness of the board of directors" (20.44%), "relations with stakeholders" (20.42%), "internal audit function ..." (20.32%) and 'salaries and benefits (18.09%). Likewise, 14% of the 70 proposed indicators obtained mean global scores higher than 3.5, which can be eliminated or analyzed in greater depth with a panel of experts. Also, the Student's t test revealed significant differences in the criteria of supervised and supervisors in four of five CG dimensions, accepting the researcher's hypothesis, which may be related to the role of the respondents.
Keywords: G28; G32; G38; 330; corporate governance; corporate governance indicators; determinantsof corporate governance; dimensions of corporate governance